“We also like to be surprised”: Disruption, provocation and surprise in the music of Christian Wolff - Thomas, Philip; Payne, Emily (Circuit)

(untitled) (Circuit, musiques contemporaines, 2020)
This article explores the ways in which the music of experimental composer Christian Wolff engenders surprise through processes of disruption and provocation. The contexts under examination are: scores which employ cueing strategies; improvisatory pieces; ensemble pieces; pieces for solo piano; and Wolff’s practice as an improvising musician. These case studies show how Wolff’s music occupies a particular position between improvisation and composition. In examining the space that Wolff’s music opens up for contingency and play, and in adopting a view of indeterminacy as understood through performance rather than limited by its notation, the article puts forward a view of indeterminacy grounded in sociality. More broadly, in its contribution to the body of literature investigating the role of notation in improvisation practices, the article invites a reconsideration of the ontological understandings of composition, improvisation, and performance.